Remote education development trends during pandemic in Russia //Tendencias de desarrollo de la educación a distancia durante la pandemia en Rusia - Kabanova, Elena E.; Vetrova, Ekaterina A.; Evstratova, Tatiana A.; Radchenko, Liudmila E. (Revista de la Universidad del Zulia, 2020)
Abstract Currently, the higher education system in Russia is in the midst of rapid changes associated with the fundamental problems of organizing the educational process during a pandemic. The pandemic of the new coronavirus infection COVID-19 in 2020 affected the educational system around the world, causing the massive closure of higher education institutions. Among the management practices of Russian universities related to the provision of security for students and staff, key decisions and recommendations based on a large-scale transition to the use of e-learning, distance learning technologies and the transition to a distance learning format, which has changed the usual way of life of university students and teachers. The objective of this research is to evaluate the transition of the educational process to distance education in the context of the pandemic, to identify the factors that hinder the development of learning. The research method is a questionnaire survey on distance learning using distance technologies in higher education. The results indicate that the development of a new model of education in universities can find resistance to external challenges and to a more productive way for economic and social development. Resumen Actualmente, el sistema de educación superior en Rusia se encuentra en medio de rápidos cambios asociados con los problemas fundamentales de la organización del proceso educativo durante una pandemia. La pandemia de la nueva infección por coronavirus COVID-19 en 2020 afectó al sistema educativo en todo el mundo, lo que provocó el cierre masivo de instituciones de educación superior. Dentro de las prácticas de gestión de las universidades rusas relacionadas con la provisión de seguridad para los estudiantes y el personal, destacan las decisiones y recomendaciones clave basadas en una transición a gran escala al uso de e-learning, tecnologías de aprendizaje a distancia y la transición a un formato de aprendizaje a distancia, que ha cambiado la habitual forma de vida de los estudiantes y docentes universitarios. El objetivo de esta investigación es evaluar la transición del proceso educativo para la educación a distancia en el contexto de la pandemia, para identificar los factores que dificultan el desarrollo del aprendizaje. El método de investigación es una encuesta de cuestionario sobre el aprendizaje a distancia que utiliza tecnologías a distancia en educación superior. Los resultados indican que el desarrollo de un nuevo modelo de educación en las universidades puede encontrar resistencia ante los desafíos externos y a una forma más productiva para el desarrollo económico y social.